Can ESPGHAN criteria be applied in the diagnosis of Celiac disease in children in Turkey?: Single-Center Experience - Güven, Burcu; Kişioğlu, Merve; Karakullukçu, Serdar; Çakır, Murat (Klinische Pädiatrie, 2025)
To investigate the applicability of the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition diagnostic criteria for celiac disease in pediatric patients in our country.This study included patients aged 1–18 years who have high tissue transglutaminase IgA antibody levels. The cut-off tissue transglutaminase IgA antibody value was expressed as times the upper limit of normality. Endomysial antibody IgA was analyzed with monkey liver tissue and the titer of the antibodies was measured. Based on the modified Marsh–Oberhuber classification, patients classified as stage III were considered to have celiac disease.Of the 416 patients, 290 (69.7%) patients were diagnosed with celiac disease. The sensitivity, specificity, positive predictive value, and negative predictive value of tissue transglutaminase IgA antibody≥10 upper limit of normality alone in the diagnosis of celiac disease were 86.5, 74.6, 88.7, and 70.7%, respectively. The tissue transglutaminase IgA antibody titer was revealed to be a significant predictor of discriminating celiac diseases from non-celiac diseases at a cut-off value of x10ULN (area under the curve=0.822, p<0.05, and 95%, confidence interval: 0.772–0.873) with a sensitivity and specificity of 86.5% and 74.6%, respectively. The sensitivity and specificity of tissue transglutaminase IgA antibody≥10ULN and endomysial antibody IgA positivity were 79.1 and 64.3%, respectively.Although European Society for Pediatric Gastroenterology, Hepatology, and Nutrition posits that most of pediatric patients with celiac disease can be diagnosed without endoscopy, it seems highly difficult to apply these criteria in our country.
Keywords: Celiac disease; ESPGHAN criteria; Turkey; pediatric